Evaluasi Sistem Proteksi Kebakaran di Gedung B PLN UID Jawa Timur - Revita Dea Sari; Deny Nurcahyo Hari Prastya; Tri Martiana; Denny Ardyanto; Parlan (Indonesian Society of Applied Science, 2026)
This study evaluates the fire protection system in Building B of PLN UID East Java. Fire incidents in work environments are often caused by electrical short circuits and improper waste burning, leading to both material and non-material losses, such as loss of life and operational disruptions. PLN UID East Java, being a vital national object, requires an effective fire protection system to safeguard against such risks. The evaluation covers three primary components: fire extinguishers (APAR), hydrants, and fire alarm systems. The evaluation methodology includes direct observation and comparison with established safety standards like NFPA 10, NFPA 14, and NFPA 72. The results showed that the APAR system met 85% of the standards, the hydrant system 83.12%, and the fire alarm system 79.29%. Despite being relatively well-equipped, there were several areas for improvement, such as updating expired fire extinguishers, providing clear hydrant usage instructions, and conducting fire alarm simulations more frequently. Enhancing these aspects is essential to ensure maximum safety for the building’s occupants and the continuity of operations.